Readings in Russian poetics formalist and structuralist views - Matejka, Ladislav 1919-2012; Pomorska, Krystyna (Ann Arbor, Michigan Michigan Slavic Publications, 1978)
A collection of the most important contributions concerning the Formalist school, most of them translated for the first time from the Russian or the Czech.
Part I. The theory of the formal method / Boris M. Èjxenbaum -- On realism in art / Roman Jakobson -- Literature and biography / Boris Tomaševskij -- Literary environment / Boris Èjxenbaum -- On literary evolution / Jurij Tynjanov -- Problems in the study of literature and language / Jurij Tynjanov, Roman Jakobson -- The dominant / Roman Jakobson -- Part II. On the boundary between studies of folklore and literature / Roman Jakobson, Petr Bogatyrev -- Fairy tale transformations / Vladimir Propp -- Part III. Contributions to the study of verse languag / Osip M. Brik -- Rhythm as the constructive factor of verse / Jurij Tynjanov -- The meaning of the word in verse / Jurij Tynjanov -- Part IV. Reported speech / V.N. Vološinov -- Discourse typology in prose / Mixail Baxtin -- Part V. Afanasij Nikitin's Journey beyond the three seas as a work of literature / Nikolaj S. Trubeckoj -- The mystery novel: Dickens's Little Dorrit / Viktor Šklovskij -- O. Henry and the theory of the short story / Boris M. Èjxenbaum -- Part VI. Russian formalism in retrospect / Krystyna Pomorska -- The formal method and linguistics / Ladislav Matejka.
Includes bibliographical references and indexes.
Keywords: Literature -- History and criticism -- Theory, etc; Formalism (Literary analysis).; Poetics